Tlingit totem pole with frog and beaver in front yard of home, Wrangell, Alaska, ca. 1904 - Nowell, Frank H., 1864-1950
Tlingit totem pole with beaver and frog in small fenced front yard of home at Fort Wrangell Alaska, ca. 1902-1906. Behind the pole is a small house. Same pole in NA2178, NA2578, NA2658 Caption on image: Totem, Ft. Wrangle, Alaska. Nowell Photo. Note from unidentified source: "Chief Kahl-teen's